2017
DOI: 10.1513/annalsats.201604-317oc
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Inhibitors and Angiotensin II Receptor Blockers and Longitudinal Change in Percent Emphysema on Computed Tomography. The Multi-Ethnic Study of Atherosclerosis Lung Study

Abstract: In a large population-based study, ACE inhibitors and ARBs were associated with slowed progression of percent emphysema by chest CT, particularly among former smokers. Randomized clinical trials of ACE and ARB agents are warranted for the prevention and treatment of emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 57 publications
1
32
0
1
Order By: Relevance
“…Our recommendations CV diseases are often underdiagnosed and under-treated in patients with COPD [18]. Furthermore, treatment with therapies targeted to treat comorbidities such as HF, IHD, AF and hypertension have the potential to modify the natural history of patients with COPD [115,124]. We therefore support the active detection and management of comorbidities in COPD and suggest using relevant treatment guidelines for patients without COPD in the absence of more specific information.…”
Section: Managementmentioning
confidence: 74%
See 1 more Smart Citation
“…Our recommendations CV diseases are often underdiagnosed and under-treated in patients with COPD [18]. Furthermore, treatment with therapies targeted to treat comorbidities such as HF, IHD, AF and hypertension have the potential to modify the natural history of patients with COPD [115,124]. We therefore support the active detection and management of comorbidities in COPD and suggest using relevant treatment guidelines for patients without COPD in the absence of more specific information.…”
Section: Managementmentioning
confidence: 74%
“…Data on the effects of RAAS inhibitors in patients with COPD are limited, although a couple of small studies have indicated a potential benefit on pulmonary function and haemodynamics [105,106]. More recently, an analysis of the Multi Ethnic Study of Atherosclerosis (MESA), including individuals in the general population aged 45-84 years who had no clinical evidence of CV disease, found that baseline use of an ACEI or ARB protected against the progression of emphysema, especially when prescribed at high doses [124]. The authors attributed the effects of such RAAS inhibitors to inhibition of transforming growth factor-β signalling in the lung, thereby reducing the progression of airspace enlargement.…”
Section: Renin-angiotensin-aldosterone System Inhibitors Aceis and Arbsmentioning
confidence: 99%
“…Angiotensin inhibition. As hypertension is a common COPD comorbidity, angiotensin‐converting enzyme inhibitors may have a dual purpose in COPD and CVD as they appear to protect against declines in lung function, particularly in individuals with CVD . Although retrospective studies demonstrate an association between angiotensin blockade and reduced mortality, large prospective studies are lacking.…”
Section: Managementmentioning
confidence: 99%
“…A recent study evaluated 4,472 participants and showed that A2RB and ACEI were associated with a slow progression of CTE 6 . However, this finding merits to be confirmed in randomized clinical trials including patients with CTE and normal FEV 1 /FVC ratio, especially considering that, to date, there is no treatment recommended for these people 2 …”
mentioning
confidence: 99%
“…, 6 Therefore, we have to pay attention to patients with CT emphysema (CTE) before they present with an altered FEV 1 /FVC ratio. However, how can we prevent the progression of CTE to GOLD-defined COPD?…”
mentioning
confidence: 99%